1994
DOI: 10.1017/s095026880005768x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial flora of Tasmanian SIDS infants with special reference to pathogenic strains ofEscherichia coli

Abstract: SUMMARYThe general bacterial flora of 38 Tasmanian SIDS infants was examined together with faecal flora of 134 comparison infants ranging in age from birth to 6 months. The microflora of all specimens received was investigated with special emphasis on the toxigenic Escherichia coli (TEC). Samples were examined for verocytotoxigenic E. coli, free faecal verocytotoxin (FVT), heat labile toxin (LT) and heat stable toxin (ST) producers with the use of a Vero cell assay and commercial kits. The findings of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Arnon et al [46] published a series of cases of infant botulism that had been misdiagnosed as SIDS. Like infant botulism (in which there is ingestion of toxigenic bacteria which colonise the gut, and the demonstration of toxin in the serum), the same model for SIDS is now supported by reasonable evidence [1][2][3][4]. Moreover and similarly, we propose that SIDS should be renamed 'infant curlinism' in recognition of our findings of curlin protein in all SIDS sera tested and our conclusion that this association is likely to be causal in nature.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Arnon et al [46] published a series of cases of infant botulism that had been misdiagnosed as SIDS. Like infant botulism (in which there is ingestion of toxigenic bacteria which colonise the gut, and the demonstration of toxin in the serum), the same model for SIDS is now supported by reasonable evidence [1][2][3][4]. Moreover and similarly, we propose that SIDS should be renamed 'infant curlinism' in recognition of our findings of curlin protein in all SIDS sera tested and our conclusion that this association is likely to be causal in nature.…”
supporting
confidence: 60%
“…Toxigenic bacteria, especially Escherichia coli in the gut or nasopharynx, have been associated with babies who have died of SIDS compared with living or dead controls [1][2][3][4][5]. Such toxic bacterial products should be demonstrable in the sera of SIDS babies.…”
mentioning
confidence: 99%
“…Independent studies have shown an increased colonisation rate by toxigenic bacteria in the gut of babies who have died of SIDS compared with healthy living babies or babies who died of other causes. [13][14][15][16] Other studies have shown nasopharyngeal colonisation by Escherichia coli 55 56 and Staphylococcus aureus, 56 with increased colonisation of the latter in infants who slept prone. 56 Furthermore, if toxins were involved in SIDS causation, these should be demonstrable in the sera of SIDS cases.…”
Section: Inflammatory Infiltratesmentioning
confidence: 99%
“…The italics are ours, and it is to suggest that more is known than is suggested in this blank statement. We and our associates (Goldwater 2001, Bettelheim et al 1989,1990, Goldwater & Bettelheim 2002, Pearce et al 1999a, 1999b, 2004 as well as others (especially Drucker et al 1992, Bettiol et al 1994, Blackwell et al 2005, Jakeman et al 1991, Malam et al 1992, Sayers et al 1995 have shown that toxigenic organisms notably ones normally considered nonpathogenic commensals may well have an important role to play in the death of these infants. There is strong evidence to support the hypothesis that SIDS is triggered by a dysregulated response to infection or microbial toxins.…”
Section: ) Evidence For Infection and Inflammation In Sids Pathogenesismentioning
confidence: 78%